2004
DOI: 10.1111/j.1460-9568.2004.03470.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of Nogo‐A in hippocampal neurons of patients with temporal lobe epilepsy

Abstract: Mesial temporal lobe epilepsy (TLE) is associated with pronounced anatomical and biochemical changes in the hippocampal formation including extensive neurodegeneration, reorganization of mossy fibres and sprouting of interneurons. Although the anatomical features and some of the physiological consequences of hippocampal remodeling have been well documented, the molecular mechanisms underlying the profound and orientated outgrowth of hippocampal neurons in TLE are not yet understood. The reticulon protein Nogo-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 58 publications
0
28
0
Order By: Relevance
“…It is generally believed that NogoA expression in adult brain is characteristic for plastic CNS regions like cortex, dorsal root ganglia and of course hippocampus [28,30,34]. In human, increased immunoreactivity of NogoA-positive hippocampal neurons was observed in Alzheimer disease [9] and temporal lobe epilepsy [3]. The increase was also present in the experimental models of brain diseases including epilepsy [28,41] or brain injury [26,28,30].…”
Section: Introductionmentioning
confidence: 61%
“…It is generally believed that NogoA expression in adult brain is characteristic for plastic CNS regions like cortex, dorsal root ganglia and of course hippocampus [28,30,34]. In human, increased immunoreactivity of NogoA-positive hippocampal neurons was observed in Alzheimer disease [9] and temporal lobe epilepsy [3]. The increase was also present in the experimental models of brain diseases including epilepsy [28,41] or brain injury [26,28,30].…”
Section: Introductionmentioning
confidence: 61%
“…Meier et al showed that Nogo-A expression is upregulated after hippocampal denervation or kainate-induced seizures (Meier et al, 2003). Studies of Bandtlow et al (Bandtlow et al, 2004) demonstrated that Nogo-A mRNA and immunoreactivity are markedly increased in hippocampal neurons of patients with temporal lobe epilepsy. In the present study, Nogo-A was found highly expressed in OLs, which is Journal of Cell Science 120 (11) consistent with previous reports (Moreira et al, 1999;GrandPre et al, 2000;Huber et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Although further investigation is needed, such genetic modifi cations may have functional signifi cance at least in a subset of patients. Finally, Nogo-A has been shown to be highly up-regulated in hippocampal neurons of patients with mesial temporal lobe epilepsy, which suggest its implication in the axonal sprouting and synaptic reorganization characteristic of the epileptic hippocampus [73] .…”
Section: Reticulons In Neurological Diseasesmentioning
confidence: 99%